La organización social orientada al desarrollo comunitario en el barrio El Condado de la ciudad de Machala - Granda Granda, Alba Violeta; Paccha Fárez, Bryan Fernando (My University, 2019)
The investigation determines the importance of the current social organization in the community development of the El Condado neighborhood of the city of Machala, from the execution of the on-site diagnostic study, in the perspective of the development of social cohesion oriented towards integral local development, describe and analyzes the results of the theoretical and empirical study, in the theoretical part the conceptions of the problem under study are developed, where the importance of the organization is highlighted in some variables such as. Functionalism as a theoretical basis for the problem under study , that as a current of social thought it states that the basic needs of people are met by social and cultural institutions, the Sociology of the organization that analyzes the relations of power and leadership and the need to organize in society. Likewise, the Social Organization and its characteristics, establish the need to organize, to organize and work together with the members of a group, is the only route to meet the needs of society, Likewise, the legal regulations referring to the problem under study that underpins the legal scaffolding that supports the research, among other variables that served to theoretically support the object of study.
La investigación determina la trascendencia de la actual organización social en el desarrollo comunitario del barrio El Condado de la ciudad de Machala, a partir de la ejecución de un estudio diagnóstico in situ, en perspectiva del fortalecimiento de la cohesión social orientada al desarrollo local integral, describe y analiza los resultados del estudio teórico y empírico, en la parte teórica se desarrolla las concepciones, del problema objeto de estudio, donde se destaca la importancia de la organización en algunas variables como. El Funcionalismo como sustento teórico del problema objeto de estudio, que como corriente del pensamiento social plantea que las necesidades básicas de las personas son satisfechas por las instituciones sociales y culturales, la Sociología de la organización que analiza las relaciones de poder y liderazgo y la necesidad de organizarse en la sociedad. Así mismo la Organización Social y sus características, permitió fundamentar la necesidad de organizarse, para ordenar y trabajar juntos con los miembros de un grupo, está es la única ruta para resolver las necesidades de la sociedad, de igual forma la normativa legal referida al problema objeto de estudio que sustenta el andamiaje jurídico que respalda la investigación, entre otras variables que sirvieron para fundamentar teóricamente el objeto de estudio.
Keywords: COHESION; ORGANIZACION SOCIAL; DESARROLLO COMUNITARIO; MACHALA